Les stations thermales secondaires de Bourgogne-Franche-Comté - Fabien Dufoulon (Les Cahiers de Framespa)
The diversity of the spa towns of Bourgogne-Franche-Comté, both in terms of management methods and architecture, make it favourable to the study of secondary sites. On the fringes of the first-rate resorts, whose size remains relatively modest on a French scale, characterized by the presence of a spa district with its casino-theater, its hotels, and its villas, the exploitation of mineral or thermal water by private entrepreneurs gave birth to secondary stations or "micro-stations" from the mid-nineteenth century onwards. Often (but not systematically) located away from the rail network and, above all, financially and legally deprived to face local competition, they struggled to develop and declined in the first decades of the early twentieth century.